Development of the scheme of combined heating system using seasonal storage of heat from solar plants - Мазуренко, Антон Станиславович; Климчук, Александр Андреевич; Юрковский, Станислав Юрьевич; Омеко, Роман Викторович (Eastern-European Journal of Enterprise Technologies, 2015)
Problems in the heat-power sector of the country force to actively introduce alternative heating systems. The most common heating systems based on renewable energy sources are solar systems and "air-water" heat pumps. Substantial unevenness of solar radiation intensity between summer and heating period requires the use of seasonal storage. A scheme for combined heating with seasonal storage of heat from the solar system was developed. The main heat storage materials, using the phase transition for the heat accumulation were presented. Climatic ranges for efficient use of various heat sources were defined. The simulation of the combined heating system was performed. Proportions of heat replacement in the combined heating system depending on heat energy sources were determined. The research data allow to significantly reduce the proportion of fossil fuels in heating systems of advanced-roofing and low-rise public buildings. The proposed scheme of combined heating allows to use different heat sources within the areas of effective application without reducing indoor comfort.